Levels of mother-to-child HIV transmission knowledge and associated factors among reproductive-age women in Ethiopia: Analysis of 2016 Ethiopian Demographic and Health Survey Data. - Mamo Nigatu Gebre; Merga Belina Feyasa; Teshome Kabeta Dadi (PLoS ONE, 2021)
Background The world community has committed to eliminating the mother-to-child transmission of human immunodeficiency virus. Even though different studies have been done in Ethiopia, to the knowledge of the investigators, the Ethiopian women's level of knowledge on the mother-to-child transmission of human immunodeficiency virus is not well studied and the existing evidence is inconclusive. The current study is aimed to study the Ethiopian women's level of knowledge on the mother-to-child transmission of human immunodeficiency virus and its associated factors using the 2016 Ethiopian Demographic and Health Survey Data. Methods Data of 15,683 women were extracted from the 2016 Ethiopia Demographic and Health Survey. Descriptive statistics and multilevel ordinal logistic regression were respectively used for the descriptive and analytical studies. Results 41.1% [95% CI: 39.5%, 42.7%] of the Ethiopian reproductive-age women have adequate knowledge of the mother-to-child transmission of human immunodeficiency virus. 77%, 84% and 87.8% of the women respectively know that human immunodeficiency virus can be transmitted during pregnancy, delivery, and breastfeeding. There are wider regional variations in the women's level of knowledge of the mother-to-child transmission of human immunodeficiency virus. Being an urban resident, having better educational status, being from a wealthy household, owning of mobile phone, frequency of listening to the radio, frequency of watching television, and being visited with field workers were significantly associated with having adequate knowledge of the mother-to-child transmission of human immunodeficiency virus. Conclusion Despite all collective measures put in a place by different stakeholders to prevent the mother-to-child transmission of HIV in Ethiopia, a large proportion of the Ethiopian women do not know about the mother-to-child transmission of the disease. Stakeholders working on HIV prevention and control should give due emphasis to promoting mobile phone technology and other media like radio and television by giving due focus to rural residents and poor women to promote the current low level of the knowledge. Emphasis should also be given to the information, education, and communication of the mother-to-child transmission of the disease through community-based educations.